A Scientometric Overview of Bioinformatics Tools in the Pseudomonas Putida Genome Study - Trentin, Alexsandro Batista; Metzner, Beatriz Thomas; Barros, Glecio Oliveira; Leite, Deborah Catharine de Assis (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Pseudomonas putida is a microorganism widely used in environmental science due to its high degradation power of recalcitrant compounds. This study aimed to perform a scientometric analysis of the global panorama of publications on the P. putida genome, in addition to the bioinformatics tools mainly used. The growth of publications on the P. putida genome is continuous until 2020, being France, Spain and USA the main countries with publications on the subject. Illumina was the main sequencing platform used and, in this set of articles, 120 genomes were sequenced, 106 complete and 14 drafts. The main assembly software was SPAdes, comprising 23.3% of the articles, and NCBI PGAP was the main genome annotation tool, in 25% of the documents. Thus, this study allowed the visualization of the main bioinformatics tools used for the analysis of the P. putida genome, besides presenting the advance of the research on this subject, and also supporting next studies with P. putida.